Shibori mentoring to empower women and foster entrepreneurial interest in Tulungrejo village, Batu city, Indonesia - Zaenab, Siti; Wahyuni, Sri; Ardiansyah, Muhammad Rifky; Iffan, Mohamad (Journal of Community Service and Empowerment, 2026)
Women in tourism villages often have limited access to creative-economy skills and market channels. This community service program aimed to strengthen women’s capacity in Tulungrejo Village (Bumiaji, Batu City) through mentoring on Shibori batik making and introductory entrepreneurship. The program used participatory training and mentoring stages: (1) socialization with the Village Head and community; (2) hands-on workshop on Shibori batik processes (folding, tying, dye mixing, waterglass fixation, drying and washing); and (3) follow-up mentoring through field visits and online consultation. Baseline information from village profiling indicates that about 30% of residents are not employed, including 1,574 people managing household work and 1,228 not working from a population of 9,251. During the first training session (27 January 2026), participation exceeded the target (18 invited; 23 attended). Participants produced Shibori fabrics with several motifs and initiated a WhatsApp group for continued practice and coordination. Qualitative feedback from interviews and reflective discussions emphasized the relevance of low-cost materials and the feasibility of home-based production. Overall, the program demonstrates early progress toward establishing a community-based Shibori batik activity that supports women empowerment and entrepreneurial interest.